Acute toxicity and anti-inflammatory activity of hydro-methanol leaves extract of Allophylus africanus Beauv in rats - Fatima S. Ibrahim; Zainab Mohammed; Aliyu Nuhu; Salisu Shehu; Najma Ilyas (Shahrekord University of Medical Sciences, 2018)
Introduction: The leaves of Allophylus africanus are traditionally used for the treatment of various ailments such as arthritis, rheumatism, gout, hemorrhoids, dysentery, venereal diseases and malnutrition. This study was carried out to evaluate the acute toxicity and anti-inflammatory activity of the hydro-methanol leaves extract of A. africanus on laboratory rats. Methods: Allophylus africanus leaves were extracted with 80% methanol using cold maceration for 5 days. The extract was subjected to phytochemical analysis, acute toxicity study and anti-inflammatory evaluation using carrageenan induced paw edema in laboratory rats. Results: The phytochemical screening of the aqueous methanol leaves extract revealed the presence of carbohydrates, tannins, steroids/triterpenes, flavonoids, alkaloids and cardiac glycosides. The extract was found to have median lethal dose (LD50) of 3807.89 mg/kg body weight orally and the aqueous methanol leaves extract at doses 250 and 1000 mg/kg produced significant anti-inflammatory effect at the 3rd, 4th and 5th hours with the effect being dose dependent at the 4th and 5th hours. There were remarkable reductions of paw edema in the rats. Conclusion: Allophylus africanus leaves has anti-inflammatory activity which explains the basis of its use in traditional medicine in the management of inflammation and related inflammatory disorders.